DIGITAL TRANSFORMATION OF ECONOMY AND TECHNOLOGICAL REVOLUTIONS: CHALLENGES FOR THE CURRENT PARADIGM OF MANAGEMENT AND CRISIS MANAGEMENT - E. P. Kochetkov (Стратегические решения и риск-менеджмент, 2020)
The digital transformation of the economy leads to dramatic changes in business and society and requires the reconfiguration of all socio-economic institutions. Such radical changes include economic science and management, challenging the traditional economic laws and management tools that were formed in the “digital era”. The purpose of the study is to identify the key challenges of the digital transformation of the economy for economic science, management and business, as well as the main directions of development of crisis management of companies in the era of the digital economy.The study identified the main factors of digital transformation of the economy that affect the methods and conditions of doing business, and the challenges of digitalization for business. The necessity of developing a new crisis toolkit for companies of the “digital” and “non-digital” eras is substantiated, for which a comparative analysis of the characteristics of such companies and key indicators of their financial and economic status is carried out. In addition author defined several economic paradoxes that the author called the “scissor effect” (a gap in the dynamics of the capitalization of digital and non-digital companies) and the “paradox of profitability” (growth in the capitalization of digital companies against the backdrop of chronic loss-making activities).Author used various methods of scientific research: deduction and induction when conducting an empirical analysis of the activities of digital and non-digital companies, analytical methods and historical analysis.The results of the study will contribute to the development of the theory of management and crisis management in the era of the digital economy, and also will determine the future directions of theoretical and practical development of these scientific disciplines.